Perception Management Through Propaganda: Nigerians' Views On Ajuri Ngelale's 'Alternative Truth' In Media Appearances On Behalf Of The Tinubu Presidency - Uwem Asuquo Akpan; George Nathan Brown; Ifeanyi Martins Nwokeocha, PhD; Aniekeme Okon Ikon, Ph.D; Vivian Ifeoma Okpalike (International Journal of Technology and Education Research, 2025)
In this age characterized and exemplified by a din of narratives jostling for public attention, this study sets out on an incisive exploration of perception management through propaganda with a specific interest in exploring the views of Nigerians on the controversial media portrayals by Ajuri Ngelale, former Special Adviser to President Bola Tinubu. Utilizing the qualitative research approach and extensive application of critical discourse analysis, the research gathers opinions from numerous groups to unveil the impact of Ngelale's 'alternative truths' on the attitude of the public and public trust in government. The conclusions consist of a pungent scepticism on the part of the public towards Ngelale's statements, as deceptive and misleading, hence promoting a disinformation culture. This loss of credibility not only tarnishes the reputation of the Tinubu administration but erodes the very fabric of Nigerian democracy. The voices of change call for a sea change towards true, responsible reporting, advocating a tighter system of vetting public spokesmen to restore trust and integrity. The stakes of this question go beyond political sloganeering, though, to the need of citizens to acquire judgment in the era of saturation with disinformation and to construct a narrative on the basis of truth and moral responsibility.